Effect Of Multiple Cracks On Gear Mesh Stiffness And Cross Correlation Of Spur Gears - Vinit Goel, Naveen Kumar, Achintya Choudhury, Sachin Lal (International Journal of Advanced Science and Technology, 2020)
An important indicator for spectrum analysis of gears is gear mesh stiffness as its value has been found to fluctuated with multiple cracks and increase in crack lengths. In the current study, the effect of multiple cracks on gear mesh stiffness and cross correlation has been investigated. Multiple cracks with different values of crack lengths and fixed input frequency, output frequency and lay frequency have been considered along these paths. MATLAB software along with FRANC 3D has been used to model the gears with multiple cracks induced. The values of mesh stiffness and cross correlation have been found to vary significantly with multiple cracks of varying crack lengths